The effect of contact aspect ratio and film to substrate elastic modulus ratio on stress vs. strain up to the point of yield during flat punch thin film indentation of an elastic-plastic film - Sinnott, Aaron D.; Brazil, Owen; Cross, Graham L. W. (Frontiers in Materials, 2022)
Nanoindentation is the only way to test the local mechanical properties of thin films and coatings. Current analysis treats the measurement as a perturbation of a conventional half-space indentation, typically limiting testing to films with modulus within an order of magnitude of the supporting substrate and contact dimension much smaller than the film thickness. In the layer compression test (LCT), a flat punch is aligned and indented into the film with a contact size much greater than the film thickness. This produces a novel test condition emulating uniform uniaxial strain even with significant penetration into the film beyond plastic yield. In this work, we perform a finite element analysis to assess the quality of this approximation in the confined elastic regime of deformation up to the point of yield via a parametric study of punch radius to film thickness ratio and film to substrate modulus ratio for a simple elastic-plastic material. Our simulations were performed with a low E/Y ratio of 10 typical of polymers, biomaterials and other amorphous systems. We find that for substrates of sufficiently high stiffness relative to the film sample, once a simple substrate stiffness correction is performed the LCT load vs. displacement slope estimates the film confined modulus to within a few percent with only minor variation throughout the entire pre-yield strain region for a wide range of aspect ratios. We also present experimental LCT findings for a supported polymer film conducted over a contact aspect ratio range of 9 to 22 and discuss the trends observed relative to the simulations.